Practitioner Profile: An Interview with Dr. Jerry Gale, LMFT - Jerry Gale (Journal of Financial Therapy, 2012)
Dr. Jerry Gale is an Associate Professor and the Clinical Director of the Marriage and Family Therapy Doctoral Program at the University of Georgia. He is a Licensed Marriage and Family Therapist and an approved supervisor of the American Association of Marriage and Family Therapists. He earned a B.A. from the University of Michigan, a MEd from the University of Arizona, and a Ph.D. from Texas Tech University. Over the course of his career, Dr. Gale has authored three books and over 60 articles and book chapters. He is a co-developer of a relational financial therapy approach that combines financial counseling with family therapy and has extensive training in clinical hypnosis, couples therapy, and family therapy, as well as mindfulness meditation. He is the recipient of the American Family Therapy Academy 2006 Outstanding Research Award. In addition to his work at the University of Georgia, Dr. Gale conducts therapy at Athens Associates for Counseling & Psychotherapy.
Keywords: marriage and family therapy; financial therapy